Solid Waste Management System Model of Village Tourism Area of Nagari Tuo Pariangan, Indonesia. Issue 1 (January 2021) - Aziz, R; Ruslinda, Y; Yeni, Y S; Dewilda, Y
Abstract: NagariTuoParianganis one of the three leading tourist attractions in Tanah Datar Regency. The increase of tourists visits NagariTuoPariangan Area has resulted in increased waste generation, improperly managed existing solid waste management endanger the environment, and sustainable development. This study aims to develop a solid waste management system model of NagariTuoPariangan as an effort to preserve the environment and support tourism development. The generation of solid waste of this area was 786, 803 kg/day, with the largest were food waste as 35% and plastic waste of 32% of total waste. The solid waste management system model considers three categories of sorting types (compostable, recyclable, and residue), while the storage use of individual type (trash bags and bin) and communal (bin 40 L, 6 m 3 containers). The collection system uses a 1.5 m 3 motorized pedicab. The processing method applies composting, enumerating plastic waste, selling paper, and metal waste to the collectors. Moreover, the residue transport using a 6 m 3 arm roll truck from the recycling center (TPS 3R) to Bukit Sangkiang Landfill. Meanwhile, the non-technical aspects planned for regulation on waste management by WaliNagari, the formation of Non-Governmental Organizations, adjusting funding according to applicable regulations, and increasing the participation of traders, communities, and visitors.